LOVE-BASED CURRICULUM CONVERGES WITH DEEP LEARNING: A QUALITATIVE STUDY OF PEDAGOGICAL TRANSFORMATION IN MADRASAH EDUCATION - Sriati; Achmad Fanani; Uswatun Qoyyimah (ELite Journal : International Journal of Education, Language and Literature, 2026)
This study examines how a Love-Based Curriculum (Kurikulum Berbasis Cinta or KBC) can be integrated with deep learning to improve teaching practices in madrasah education. The study focuses on how values such as love, empathy, respect, and care are embedded in curriculum planning and classroom learning to create meaningful learning experiences for students. A qualitative case study was conducted at a public Islamic senior high school (madrasah) in Indonesia. Data were collected through semi-structured interviews, classroom observations, and document analysis involving teachers, school leaders, and curriculum coordinators. The findings show that integrating the Love-Based Curriculum with deep learning encourages teachers to move beyond simply delivering subject content. Instead, they design learning activities that help students think critically, reflect on their experiences, and develop social, emotional, and spiritual values. Teachers also became more focused on supporting students' individual learning needs and active participation. However, the study identified several challenges, including limited teacher readiness to implement reflective teaching practices and the need for stronger curriculum management. Overall, the findings suggest that integrating love-based values with deep learning can strengthen teaching quality in Islamic education. Within this pedagogical framework, technology can serve as a valuable tool for supporting teachers' lesson planning, assessment, and reflective practice, provided that it remains aligned with the curriculum's core principles of care, empathy, and meaningful human relationships rather than replacing them.